(untitled) (Research, Society and Development, 2022)
Recommendations to guide the nutritional care of critically ill patients affected by Coronavirus have been published in recent years. However, there are few reports on the establishment of the new routine of nutritional care and monitoring in the hospital setting. The objective of this article is to present the implementation of a protocol with care flow and nutritional routine of a nutrition service, for patients in the intensive care unit of a reference hospital for COVID-19. This is an experience report that presents the routines of the nutrition care service, which were organized for the care of patients during the pandemic of COVID-19, according to recommendations proposed by national and international entities. In the first stage of care, screening for nutritional risk and checking the level of care were performed to guide the frequency of nutritional monitoring. The calorie and protein needs were calculated according to individual nutritional diagnosis. For nutritional therapy use, the oral or enteral route was prioritized for feeding and procedures for special situations, such as prone position, were standardized. In the first 30 days of the hospital’s operation, all nutritional assistance was provided non-presentially, with standardized protocols, which were later revised and adapted to be used in face-to-face care, but still without physical contact of nutritionists with patients. Thus, the production and review of institutional flows, adapting them to the scientific updates published during the pandemic, allowed for the qualification of the nutritional assistance provided in the reference hospital for COVID-19.